Phytochemical and Antimicrobial Activity of Methanolic Leaf Extract of Eclipta prostrata L.: Life Sciences-Phytochemistry - Shrawani; Verma, Kanhaiyaji (International Journal of Life Science and Pharma Research, 2022)
Eclipta prostrata L. is a widely distributed medicinal plant belonging to the Asteraceae family. The plant is rich in many volatile compounds and several bioactive components that aid the potential pharmacological activity of the plant. The knowledge about the presence of such bioactive compounds in plants is important to derive the application and economic importance of such plants. The present study aims to evaluate the phytochemical profile of E. prostrata L.by the qualitative and quantitative methods. The phytochemical profiling was done by standard screening procedure, while the antimicrobial potential in the methanolic leaf extract was determined by the agar well diffusion method. The phytochemical profiling revealed that the methanolic leaf extract contains phenols, alkaloids, flavonoids, glycosides, and saponins. The leaf extract is also a rich source of alkaloids, phenols, carbohydrates, and reducing sugars as suggested by the quantitative analysis. The methanolic extract at its low concentration of 50mg/ml was found to be effective against the selected bacterial pathogens and among them it was highly effective against Staphylococcus aureus. But the extract lacked any antifungal potential against selected isolates, Candida albicans, and Aspergillus flavus. The study emphasizes the pharmacological importance of the selected plant by revealing its potential bioactive compound profile and its antimicrobial activity. In future, the investigation can focus on determining the phytochemical profile of the plant in other solvent systems. Isolation, purification, and application of the active constituent can be studied further. The compound profile of extracts could reveal the exact information of the metabolites present in them, which will help derive its applications. This information could help deduce the methodology to purify or concentrate the respective bioactive compound in the extract of E. prostrata L.